The Heterogeneous Effects of HIV Testing - Baird, Sarah; Gong, Erick; McIntosh, Craig; Özler, Berk (World Bank, Washington, DC, 2014)
An extensive multi-disciplinary literature examines the effects of learning one's HIV status on subsequent risky sexual behaviors. However, many of these studies rely on non-experimental designs; use self-reported outcome measures, or both. This study investigates the effects of a randomly assigned home based HIV testing and counseling (HTC) intervention on risky sexual behaviors and schooling investments among school-age females in Malawi. The study finds no overall effects on HIV, Herpes Simplex Virus (HSV-2), or achievement test scores at follow-up. However, among the small group of individuals who tested positive for HIV, a large increase in the probability of contracting HSV-2 is found, with this effect stronger among those surprised by their test results. Similarly, those surprised by HIV-negative test results see a significant improvement in achievement test scores, consistent with increased returns to investments in human capital. The finding of increased HSV-2 prevalence among HIV-positive individuals suggests that the conventional wisdom that those who learn they are HIV-positive will adopt safer sexual practices should be treated with caution.